Islam and Higher Education : Concepts, Challenges and Opportunities. - Muborakshoeva, Marodsilton (Routledge contemporary South Asia series., 2012)
This book is the first study to qualitatively explore the concepts of higher education in Muslim contexts. It examines the different concepts of 'a university' and the way they shape practice in Muslim contexts, with a particular focus on the Islamic republic of Pakistan. Contributing to theoretical debates and discussing practical challenges that universities in Muslim countries face, the author analyses seven higher education institutions in Pakistan. She argues that there is a need for institutions to constantly review their mission and aims and objectives in light of the wider economic, po.